Design resistance of high strength steel square hollow section K-joints - Zuo, Fei (2016)
Steel is widely used in modern building constructions and consequently, extensive research on steel structure is carried out all around the world. Among steel structures, the use of high strength steel is gaining popularity and wider usage. The exact effect of using the high strength steel on the strength of joints has not been investigated extensively so far and there are no published design equations available at present. This study will investigate the influence of steel grade on the strength of Square Hollow Section K-joints. The results from this study mainly will complement the on-going research on the MND-SUL project. In the MND-SUL project, a functional truss bridge across an express way is planned to be built and the mega-truss will be made of S690 steel sections. This thesis presents the numerical studies for assessing the strength of high strength steel SHS gap K-joints. The aim of the numerical analysis is to improve the current design equation in CIDECT Design Guide 3. The results demonstrate the influence of high strength steel on the design resistance of K-joints and two new formulas are proposed to improve the existing equation. Two finite element models are validated with experimental results as the basic verification step. The parametric study is conducted which comprises 60 models of SHS K-joints made of S690, 60 models of gap SHS K-joints made of S355 and 60models of SHS K-joints made of S460. Each model is subjected to 3 load cases. The geometric parameters for the joints such as width ratio between braces and chord (β), half width to thickness ratio of chord (γ), the thickness ratio between braces and chord (τ) are varied in the parametric study. The higher the preload is, the lesser the strength of gap SHS K-joints observed. It is found that chord face failure by yielding or buckling is the most common type of failure for β of 0.6 to 0.8, 2γ of 30 to 35 and τ of 0.79 to 1. The numerical results are compared to existing formula in CIDECT Design Guide 3. It is found that the numerical ultimate capacity of the joints is less than the theoretical results predicted by CIDECT Design Guide 3. Two parametric formulas for predicting the design resistance of gap SHS K-joints with high strength steel are proposed in the thesis. The results of proposed formulae are compared with the numerical results and they show good agreement.